The Relationship between Fatigue and The Incidence of Tension-Type Headache in The First Semester Resident Doctors of The Faculty of Medicine Universitas Sumatera Utara - Rozi, Fakhrur; Surbakti, Khairul Putra; Nasution, Irina Kemala (Journal of Society Medicine, 2023)
Introduction: Tension-type headache (TTH) is one of the major public health concerns globally with an incidence of 1.89 billion people. Fatigue is potentially debilitating and affects an individual's quality of life and is known to be associated with the case of TTH. The purpose of this study was To find out the relationship between fatigue and the incidence of tension-type headache in the first semester resident doctors of the Faculty of Medicine Universitas Sumatera Utara. Method: The research design was an observational study with a cross-sectional approach which was undertaken at Haji Adam Malik Hospital and Network Hospital in January to February 2022 with all first semester resident doctors as research subject at Faculty of Medicine, Universitas Sumatera Utara in the period of August 2022. Fatigue was measured through the Fatigue Severity Scale (FSS), TTH frequency was measured using the third of the International Classification of Headache Disorders (ICHD-3) criteria, and TTH pain intensity was measured using numerical rating scale (NRS). Meanwhile, to analyze the relationship between fatigue and the incidence of tension-type headache, the Spearman correlation test was used. Results: : Total subjects who met the inclusion and exclusion criteria was 98.  Regarding to the results of statistical tests, a significant relationship was obtained between fatigue and TTH frequency (r= 0,294, p= 0,003), but there was no relationship between fatigue and the pain intensity (r= 0,143, p= 0,160). Conclusion: There was a significant relationship between fatigue and TTH frequency. However, the relationship was not significant between Fatigue and the pain intensity